PERKEMBANGAN SOSIAL EKONOMI KABUPATEN SIAK PADA ERA PEMEKARAN DAERAH TAHUN 2000-2014 - Melay, Ridwan Melay Ridwan; ', Astrilla Astrilla; ', Tugiman Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: There is uneven development and a lack of attention to public welfare causes Siak which formerly was part of Bengkalis decided to expant a new district. Exspansion Siak District of Bengkalis certainly lead to the development of the social and economic life in the community. In the field of socio-economic, such as education, health, employment and income. If adequate facilities and equitable development it will be able to have an impact on the welfare of the community. This study aims to determine the expansion history Bengkalis Siak regency, to know the development of Infrastructures education in Siak on regional expansion era in 2000-2014, to determine the development of health Infrastructures in Siak on regional expansion era in 2000-2014, to determine the development of jobs in Siak on Regional expansion era in 2000-2014, to determine the development of revenue in Siak district in the era of regional expansion in 2000-2014. The theory used in this research is the theory of the expansion of regions, autonomous regions, Expansion area, the impact of regional division, the socio-economic dimension. This research uses descriptive and qualitative research methods. The data collected in this research using secondary data will be processed by the tabulation frequency time series will then be deduced. The results showed Expansion of area occurs in Siak district, namely the expansion of Bengkalis is one of regencies in Indonesia who managed Proliferation Siak able to increase the potential of the area resulting in socio-economic changes towards a better order to accelerate the realization of public welfare.Keywords: Expansion, Socio-Economic, Siak District